Strain indicators in the assessment of systolic myocardial function in aboy with hypertrophic cardiomyopathy: a case report - Nadezhda Chernykh; Alla Tarasova; Olga Groznova (Acta Medico-Biotechnica, 2021)
Purpose: This article is about an unusual clinical case of a 14-year-old boy with hypertrophic cardiomyopathy (HCM).Ejection fraction (EF) and shortening fraction (FS) of the left ventricle in children with HCM remain within a normal range for an extended period of time. Therefore, detection of a decrease in segmental myocardial contractility at the initial stage of the disease presents a diagnostic problem.Methods: The clinical characteristics of the patient, study results, and analysis of the left ventricular myocardial strain using 2D speckle-tracking mode in an echocardiographic examination are presented.Results: A decrease in strain indicators in the anterioseptal, anterior, and anterolateral segments of the left ventricular myocardium and a compensatory increase in the contralateral segments were revealed. This served as an indication to start treatment.Conclusions: A decrease in strain indicators in the 2D speckle- tracking mode is most informatively represented by changes in segmental systolic function of the left ventricle at the initial stage of HCM.